Prevalence and socioeconomic correlates of depression, anxiety and stress among undergraduate students from reserved social categories in a rural college of West Bengal: a cross-sectional study - Kousik Nag; Jayita Pal; Sanjoy Kumar Sadhukhan; Dhiren Kumar Ruidas; Vibhuti Vaibhav; Arindam Chatterjee (International Journal Of Community Medicine And Public Health, 2026)
Background: Common mental disorders such as depression, anxiety and stress are increasingly reported among young adults, particularly college students. Evidence from India suggests that socio-economic disadvantage and social stratification may influence mental health outcomes; however, limited data exist focusing specifically on students from socially reserved categories. This study aimed to estimate the prevalence of depression, anxiety and stress and to examine their socio-demographic correlates among undergraduate students belonging to reserved social categories in a rural college of West Bengal. Methods: A census-based cross-sectional study was conducted among 176 undergraduate students aged 18–24 years belonging to Scheduled Castes, Scheduled Tribes and Other Backward Classes in a government college of Purulia district. Data were collected using a pretested questionnaire and the Depression Anxiety Stress Scale-21 (DASS-21). Scores were categorized using standard cut-offs. Associations between socio-demographic variables and outcomes were assessed using the chi-square test, with p